2022
DOI: 10.1111/joca.12476
|View full text |Cite
|
Sign up to set email alerts
|

Social media and mindfulness: From the fear of missing out (FOMO) to the joy of missing out (JOMO)

Abstract: Mindless use of social media may lead to negative mental health outcomes for consumers. In this research, the authors focus on the fear of missing out (FOMO) as a key determinant of those negative outcomes by illustrating how repeated social media use forms a habit loop termed "social media FOMO." The authors introduce a "Social Media FOMO to JOMO" framework, where they describe how mindless use can

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…The results of this study suggest that attention control and fear of missing out partially mediate the relationship between mindfulness and social media addiction. Consequently, in this study, we confirmed a direct link between mindfulness and social media addiction in Chinese college students ( 38 ). We found that mindfulness, through three paths, influence social media addiction, and that these three paths are: attention control, fear of missing out, and attention control → fear of missing out.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The results of this study suggest that attention control and fear of missing out partially mediate the relationship between mindfulness and social media addiction. Consequently, in this study, we confirmed a direct link between mindfulness and social media addiction in Chinese college students ( 38 ). We found that mindfulness, through three paths, influence social media addiction, and that these three paths are: attention control, fear of missing out, and attention control → fear of missing out.…”
Section: Discussionsupporting
confidence: 81%
“…Impaired attention control makes individuals more likely to skew attentional resources toward threatening information in the presence of anxiety (52). As an anxious emotion, the negative association between FOMO and attention control has been verified by previous studies (26,38,53).…”
Section: The Serial Mediating Role Of Attention Control and Fomosupporting
confidence: 80%
See 2 more Smart Citations
“…Mindfulness has been suggested as an antidote to mindless consumption, as it leads to better decision making (Bahl et al, 2013, Bahl et al, 2016; Chan et al, 2022; Milne et al, 2020; Sheth et al, 2011). Furthermore, mindfulness is commonly understood as the awareness arising when one pays attention in a nonjudgmental manner (Kabat‐Zinn, 1990).…”
Section: Introductionmentioning
confidence: 99%